The Malays - Milner, Anthony Crothers 1945- (Peoples of South-East Asia and Pacific, 2008)
Just who are the Malays? This provocative study, now available in paperback, poses the question and considers how and why the answers have changed over time, and from one region to another. Anthony Milner develops a sustained argument about ethnicity and identity in an historical 'Malay' context.